A computer-supported methodology for requirements modelling in CIM for small and medium size enterprises: A demonstration in Apparel Industry - Hashemipour, M; Anlagan, O; Kayaligil, S (Taylor & Francis Ltd, 1997)
This paper discusses the first phase of a computer-assisted methodology for implementing CIM within small and medium enterprises. Some of the existing methodologies and tools were furnished by extra items to ease the process for small and medium size manufacturing companies. The methodology aims at using limited expertise, limited staff, and minimising cost. The existing analysis tools (i.e. DFDs, ELH, and tools in the GRAI methodology) were modified and a new tool was developed (PIFR) to shed light on the needs (and new forms) of integration of material and data flows in various parts of the organization. A knowledge base is developed for portability and ease of use. To demonstrate the methodology, a case study was carried out in a firm in apparel industry.
Keywords: Design; Implementation; Integration; Systems